Prolonged moderate to vigorous physical activity may lead to a decline in cognitive performance: a Mendelian randomization study - Li, Yutao; Fu, Chenyi; Song, Honglin; Zhang, Zhenhang; Liu, Tianbiao (Frontiers in Aging Neuroscience, 2024)
Objective This study investigates the causal relationship between moderate to vigorous physical activity and cognitive performance. Methods Genetic loci strongly related to moderate to vigorous physical activity from genome-wide association studies were used as instrumental variables. These were combined with genetic data on cognitive performance from different Genome-Wide Association Study (GWAS) to conduct a two-sample Mendelian randomization analysis. The primary analysis used inverse variance weighting within a random effects model, supplemented by weighted median estimation, MR-Egger regression and other methods, with results expressed as Beta coefficient. Results This study selected 19 SNPs closely related to physical activity as instrumental variables. The multiplicative random-effects Inverse-Variance Weighted (IVW) analysis revealed that moderate to vigorous physical activity was negatively associated with cognitive performance (Beta = −0.551; OR = 0.58; 95% CI: 0.46–0.72; p < 0.001). Consistent results were obtained using the fixed effects IVW model (Beta = −0.551; OR = 0.58; 95% CI: 0.52–0.63; p < 0.001), weighted median (Beta = −0.424; OR = 0.65; 95% CI: 0.55–0.78; p < 0.001), simple mode (Beta = −0.467; OR = 0.63; 95% CI: 0.44–0.90; p < 0.001), and weighted mode (Beta = −0.504; OR = 0.60; 95% CI: 0.44–0.83; p < 0.001). After adjusting for BMI, smoking, sleep duration, and alcohol intake frequency, the multivariate MR analysis also showed a significant association between genetically predicted MVPA and cognitive performance, with Beta of −0.599 and OR = 0.55 (95% CI: 0.44–0.69; p < 0.001). Conclusion The findings of this study indicate that genetically predicted moderate to vigorous physical activity may be associated with a decline in cognitive performance.